Is the French SIRE equine information system a good basis for surveillance and epidemiological research? Quality assessment using two surveys. (January 2021) - Farchati, Halifa; Merlin, Aurelie; Saussac, Mathilde; Dornier, Xavier; Dhollande, Mathilde; Garon, David; Tapprest, Jackie; Sala, Carole
Abstract: Accurate demographic knowledge of the equine population is needed to assess and model equine health events. France is one of the few European countries with an operational centralized database (SIRE) recording individual data on all declared equines living in France and on their owners and keepers. Our study aimed to assess SIRE database quality concerning the updating of information by equine owners and keepers with a view to its improvement and use in surveillance and research. Two online surveys were conducted with the participation of 6244 registered keepers and 13, 869 owners. Results showed some inconsistencies between SIRE records and survey responses. The inconsistency rate for equines whose castration and death were not registered in the database was 28.7% and 5.9% respectively. Concerning owners, 11% of respondents did not own the reference equine selected considered by the survey, 33% had changed address without updating it in the SIRE. Concerning premises hosting equines, the keeper survey's inconsistency rate was 7.3%, of which 57 respondents had closed and 32 had opened premises without reporting it. Comparatively, the owner survey's inconsistency rate was 40.7% including respondents who owned and hosted an equine without reporting these equine premises, and owners who did not keep any equines on their premises. In conclusion, the SIRE database proved to be a valuable and reliable source for epidemiological research as long as some bias is taken into account. On the contrary, its use in surveillance is currently limited due some shortcomings in updating and/or reporting by owners and keepers. Highlights: The SIRE database is a valuable source for epidemiological studies. Some biases must be taken into account during epidemiological modeling. Better reporting of equine deaths should be strongly encouraged. Regular updating of contact details by keepers would be a major improvement.